The Association of Complements, TGF-β, and IL-6 with Disease Activity, Renal Damage, and Hematological Activity in Patients with Naïve SLE - Yuliasih Yuliasih; Lita Diah Rahmawati; Nabilatun Nisa’; Cahaya Prastayudha (International Journal of Inflammation)
Several key player factors, such as cytokine and complement, play an important role in the pathogenesis of systemic lupus erythematosus (SLE). The purpose of this study was to reveal the association between complement 3 (C3), complement 4 (C4), interleukin-6 (IL-6), and transforming growth factor-β (TGF-β) with SLE disease activity, renal damage, and hematological activity in patients with naïve SLE. The Laboratory of Clinical Pathology Dr. Soetomo General Hospital in Surabaya performed all laboratory examinations on thirty women with naïve SLE. The SLE diagnosis is based on ACR criteria (1998 revised criteria) from Dr. Soetomo General Hospital Surabaya, Indonesia, and the systemic lupus activity measurement (SLAM) score is used to assess the disease activity. The correlation was statistically tested using the Spearman and Pearson tests. The differences in cytokine and complement levels are between SLE severity groups using the two-way Anova and Kruskal–Wallis. The unpaired T-test and Mann–Whitney test were used to determine the differences between the relatively normal and the more severe groups of organ damage and hematological activity. All tests were two-tailed, analyzed with GraphPad Prism 9 for windows, and a p value of less than 0.05 was considered statistically significant. This study found a significant decrease in C3 (20.2, 16.4–24.2 mg/dL) and C4 (7, 6–14.3 mg/dL) and an increase in IL-6 (35.60 ± 7.43 mg/dL) and TGF-β (311.1 ± 290.8 mg/dL) in the group of severe patients with SLAM scores >30. Although there is no significant relationship between SLAM and renal impairment or hematologic activity, patients with higher SLAM had a significant decrease in complement; this complement decrease was also significant in patients with higher leukocyte counts. An insignificant increase in cytokines was also observed in patients with higher SLAM. Patients with high serum creatinine levels had a significant increase in TGF-β, whereas those with a faster ESR had a significant increase in IL-6. In conjunction with complements evaluation, assessment of the cytokine profile may become a promising marker for reliable diagnosis and treatment of SLE in the future.